Organizational Learning, Inovasi Organisasi, Manajemen Pengetahuan, dan Kinerja Organisasi - Sudrajat, Sudrajat; Astarika, Rina (Akmenika: Jurnal Akuntansi dan Manajemen, 2025)
This empirical research aims to determine the relationship between organizational learning, organizational innovation, knowledge management, and organizational performance in manufacturing and service companies. 197 data that can be analyzed using SPSS. The findings of this study: organizational learning has a direct and positive effect on knowledge management in manufacturing and service companies. Organizational learning and knowledge management directly influence organizational innovation. While organizational learning and organizational innovation directly affect organizational performance. Knowledge management and organizational learning affect organizational performance indirectly through organizational innovation.